03 ANALISIS FAKTOR PENDAPATAN YANG BERPENGARUH TERHADAP USAHATANI CABAI BESAR (Studi Kasus Desa Sawaru Kecamatan Camba Kabupaten Maros) - Jurnal Agribis; Muhammad Rizal Syam; Arifin Arifin; Mohammad Anwar Sadat (Jurnal Agribis, 2017)
The research objective is: to determine the income factors that affect large chilli farmers in Sawaru Village, Camba District, Maros Regency. The sampling technique in this study is all farmers who are trying to have large chillies of up to 45 people, out of the population the number of samples taken is 50% then the number of samples is 23 people with a random sampling technique. Based on the results of the analysis presented in Table 1, it is known that the coefficient of determination (R-squared) of 0, 961, this means 96.10 percent of income variables large chili can be explained by independent variables (land area, age, and experience of farming). Based on the results of research and discussion, it can be concluded that the factors affecting the income of large chili farmers are the area of land and the age of the farmer.